The physics of ice - Pounder, Elton Roy (Commonwealth and international library of science, technology, engineering, and liberal studies. Geophysics division), 1965)
The Physics of Ice covers the state of knowledge regarding the structure, properties, occurrence, and movement of ice. This book is composed of eight chapters, and begins with an introduction and in the fundamental aspects of ice, including pure water freezing, circulation, occurrence, classification, and importance of ice. The subsequent chapters describe the properties, structure, freezing, and composition of sea ice and ice drift. These topics are followed by discussions on the crystallographic features, and mechanical, thermal, and electrical properties of ice. The concluding chapter exam.